Application of Leslie Matrix in The Calculation of Female Population Prediction in Padang City, Indonesia - Rahma Yunita (Journal of Applied Mathematics and Modelling, 2025)
The Leslie Matrix is a mathematical tool widely used to model population dynamics based on fertility and survival rates across age classes. This study applies the Leslie Matrix to predict the female population in Padang City using demographic data from Padang Dalam Angka (BPS, 2020-2021). The model incorporates fertility rates, survival probabilities, and age-structured population data to construct a 16x16 Leslie Matrix. The dominant eigenvalue obtained was 0,3183, indicating that the female population in Padang City is projected to decline over time. Predictions show a population decrease from 450,154 in 2021 to 425,875 in 2024. These findings highlight the declining growth trend of the female population in Padang City and suggest the importance of demographic monitoring for urban planning and social policy.